pharmaceutical-sciences 2018
DOI: 10.4172/pharmaceutical-sciences.1000327
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Antioxidant and Antimicrobial Screening of Suaeda maritima L (Dumort) against Human Pathogens and Multiple Drug Resistant Bacteria

Abstract: The problem of antibacterial resistance to frequently used antibiotics has led to a search for newer and alternative compounds for the treatment of drugresistant infections [1]. Although pharmaceutical companies have designed a number of new antibiotics in the last three decades, resistance against these drugs by microorganisms has also been observed. Drug resistant bacterial infections are causing immense mortality and morbidity worldwide. For example, in 2005, in the United States, 19 000 out of 95 000 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Because of the production of varied types of bioactive compounds, use of mangroves as potent source of antimicrobials (Beula et al, 2012), insecticides (Suresh et al, 2017), antidiabetic (Nabeel et al, 2010), anticancer (Eswaraiaha et al, 2019), and antioxidants (Banerjee et al, 2008;Wangensteen et al, 2009) have been reported. Among the global mangroves, Suaeda species of Chenopodiaceae family occupies a special position and are known to be the producers of antibacterial (Patra et al, 2009;Muthazhagan et al, 2014;Nayak et al, 2018), antifungal (Boughalleb et al, 2009), mosquitocidal (Suresh et al, 2017), anticancer (Oueslati et al, 2012), hepatoprotective (Ravikumar et al, 2011), phytotoxic (Ali et al, 2014;Khan et al, 2018), diuretic (Kakrani and Saluja, 2001) and antioxidant (Oueslati et al, 2012) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the production of varied types of bioactive compounds, use of mangroves as potent source of antimicrobials (Beula et al, 2012), insecticides (Suresh et al, 2017), antidiabetic (Nabeel et al, 2010), anticancer (Eswaraiaha et al, 2019), and antioxidants (Banerjee et al, 2008;Wangensteen et al, 2009) have been reported. Among the global mangroves, Suaeda species of Chenopodiaceae family occupies a special position and are known to be the producers of antibacterial (Patra et al, 2009;Muthazhagan et al, 2014;Nayak et al, 2018), antifungal (Boughalleb et al, 2009), mosquitocidal (Suresh et al, 2017), anticancer (Oueslati et al, 2012), hepatoprotective (Ravikumar et al, 2011), phytotoxic (Ali et al, 2014;Khan et al, 2018), diuretic (Kakrani and Saluja, 2001) and antioxidant (Oueslati et al, 2012) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…About 1600 mangrove plant species are available in India and Suaeda maritima is one among them. It is used as an ethno medicine for curing various ailments such as hepatitis, bacterial infections, chronic inflammation and oxidative stress diseases (Nayak et al 2018). It is a salt marshy mangrove plant that belongs to the family Chenopodiaceae and subfamily Suaedoideae and popularly known as seep weeds/sea-blites due their existence in coastal salt-flats and tidal wetlands (Kumar et al 2019a, b).…”
Section: Introductionmentioning
confidence: 99%
“…All the four extracts have shown the presence of various secondary metabolites, where in majority of active constituents were present in ethanolic and aqueous extracts. Nayak et al (2018) reported presence of saponins, terpenoids, tannins, alkaloids and steroids in the methanol leaf extracts of Suaeda maritima, besides their presence in other mangroves such as Xylocarpus granatum, Avicennia marina, Salvador apersica and Avicennia o cinalis (Mulla and Chavan 2016). Similar to present study, ethanolic extract of Sesuviumportula castrum possesses phytochemicals like alkaloids, carbohydrates, cardiac glycosides, avonoids, phenols, saponins, sterols, terpenoids, quinones, diterpenes, and resins contributed to its therapeutic value (Chintalapani et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…About 1600 mangrove plant species are available in India and Suaeda maritima is one among them. It is used as an ethno medicine for curing various ailments such as hepatitis, bacterial infections, chronic in ammation and oxidative stress diseases (Nayak et al 2018). It is a salt marshy mangrove plant that belongs to the family Chenopodiaceae and subfamily Suaedoideae and popularly known as seep weeds/sea-blites due their existence in coastal salt-ats and tidal wetlands ).…”
Section: Introductionmentioning
confidence: 99%